2022
DOI: 10.1186/s12905-022-01948-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic pelvic pain and primary dysmenorrhea in women of reproductive age in Ecuador

Abstract: Background Chronic pelvic pain (CPP) and primary dysmenorrhoea are debilitating conditions that can impair the quality of life of affected women. These conditions are frequently neglected, delaying proper diagnosis and healthcare provision. This study aimed to estimate the prevalence of CPP and primary dysmenorrhoea in Ecuador and identify potential variables associated with their occurrence. Methods We conducted a cross-sectional survey in an urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
4
1
2
1
Order By: Relevance
“…This data points out that the item deserves attention, as some women avoid sexual activity because of pain, sexual dysfunction, or the absence of a partner. It corroborates what the literature suggests, namely that women with CPP have higher dyspareunia rates 32 , sexual dysfunction is more common, and they have worse rates in most domains of the FSFI (Female Sexual Function Index) 33 , generating a negative impact on female sexual function 34 . The WHODAS 2.0 showed excellent reproducibility indices in the studied population.…”
Section: Resultssupporting
confidence: 88%
“…This data points out that the item deserves attention, as some women avoid sexual activity because of pain, sexual dysfunction, or the absence of a partner. It corroborates what the literature suggests, namely that women with CPP have higher dyspareunia rates 32 , sexual dysfunction is more common, and they have worse rates in most domains of the FSFI (Female Sexual Function Index) 33 , generating a negative impact on female sexual function 34 . The WHODAS 2.0 showed excellent reproducibility indices in the studied population.…”
Section: Resultssupporting
confidence: 88%
“…In our study, the prevalence of non-cyclical pelvic pain was similar to that observed in Latin American countries such as Brazil, where it's close to 10% (61, 62), and in urban communities of Ecuador, where it is 8.9% (50). It was positively associated with various other painful conditions, reinforcing the link between the condition and nociplastia (63), and perhaps re ecting the clinical expression of central sensitization that commonly occurs in this group of patients (64).…”
Section: Discussionsupporting
confidence: 84%
“…The observed prevalence of dyspareunia in this population was signi cantly lower than that previously reported in the urban population of Ecuador (50). The exact reason for this difference remains uncertain.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…A pontuação média da END no dia da avaliação foi de 6,03±3,02; n=86, e a média do último mês foi de 7,49±2,17; n=57 (Tabela 1). 32 , a disfunção sexual é mais comum e elas têm piores índices na maioria dos domínios do FSFI (Female Sexual Function Index) 33 , gerando um impacto negativo na função sexual feminina 34 . O WHODAS 2.0 apresentou excelentes índices de reprodutibilidade na população estudada.…”
Section: Resultsunclassified